2000
DOI: 10.7182/prtr.10.4.q145251v4v26h833
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation in a patient at psychosocial risk

Abstract: Psychosocial assessment of transplant candidates is a challenging task. Securing adequate information is made more difficult when patients present with fulminant hepatic failure. When the patient cannot be interviewed and the family is reluctant to provide vital information, a comprehensive pretransplant psychosocial evaluation is virtually impossible. However, even the most difficult cases have the potential for a positive result when a good psychosocial profile of the patient is obtained after transplantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…What little research is available provides some support for clinical assumptions that patients with certain personality disorders, substance use disorders, poor coping skills, poor compliance, and poor social supports can have worse posttransplant outcomes. Nevertheless, case reports have demonstrated that even some patients who might seem inappropriate for transplant (e.g., patients with active psychosis or with severe personality disorders) (Carlson et al 2000;DiMartini and Twillman 1994) can undergo transplantation and maintain adequate compliance after the procedure. Such patients should be carefully assessed pretransplant with optimization of their pretransplant condition and ongoing psychiatric monitoring and treatment posttransplantation.…”
Section: Controversial Psychosocial and Psychiatric Issuesmentioning
confidence: 97%
See 2 more Smart Citations
“…What little research is available provides some support for clinical assumptions that patients with certain personality disorders, substance use disorders, poor coping skills, poor compliance, and poor social supports can have worse posttransplant outcomes. Nevertheless, case reports have demonstrated that even some patients who might seem inappropriate for transplant (e.g., patients with active psychosis or with severe personality disorders) (Carlson et al 2000;DiMartini and Twillman 1994) can undergo transplantation and maintain adequate compliance after the procedure. Such patients should be carefully assessed pretransplant with optimization of their pretransplant condition and ongoing psychiatric monitoring and treatment posttransplantation.…”
Section: Controversial Psychosocial and Psychiatric Issuesmentioning
confidence: 97%
“…By identifying personality traits and disorders, the psychiatrist can potentially predict patterns of behavior, recommend treatment, develop a behavioral plan with the team to work constructively with the patient, and render an opinion as to the candidate's ability to proceed with transplantation. Patients with personality disorders can require excessive amounts of time from the transplant team, which raises the issue of resource allocation as a potential selection criterion (Carlson et al 2000). Not surprisingly, a majority of programs (50%-60% across organ types) consider personality disorders to be a relative contraindication to transplantation (Levenson and Olbrisch 1993).…”
Section: Personality Disordersmentioning
confidence: 98%
See 1 more Smart Citation
“…Para los pacientes con contraindicación relativa, el comité de transplante deberá valorar la capacidad del paciente para seguir de forma adecuada los controles médicos y la toma de medicación después del trasplante 43 . En los trastornos susceptibles de tratamiento, se iniciará un tratamiento farmacológico y un seguimiento de unas 3-4 visitas.…”
Section: Pacientes Con Trastornos Psicopatológicosunclassified
“…As such, concerns have been raised in regards to subsequent compliance with medication and medical follow‐up in such individuals with an impact on long‐term outcome following LT (7, 8). Additionally, given the rapid evolution of hepatic encephalopathy (HE) in this condition, a comprehensive pretransplant psychosocial evaluation as undertaken before elective surgery is frequently impossible (9). Finally, the progression from isolated hepatic failure to refractory multiple organ failure and the development of contraindications to surgery occurs more rapidly than in patients presenting with ALF of other aetiologies, allowing a narrow opportunity for successful transplantation (10).…”
mentioning
confidence: 99%